2021
DOI: 10.3390/ijerph18094766
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Spread of the SARS-CoV-2 Variant of Concern 202012/01 in Southern Italy (December 2020–March 2021)

Abstract: Epidemiological and virological studies have revealed that SARS-CoV-2 variants of concern (VOCs) are emerging globally, including in Europe. The aim of this study was to evaluate the spread of B.1.1.7-lineage SARS-CoV-2 in southern Italy from December 2020–March 2021 through the detection of the S gene target failure (SGTF), which could be considered a robust proxy of VOC B.1.1.7. SGTF was assessed on 3075 samples from week 52/2020 to week 10/2021. A subset of positive samples identified in the Apulia region d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Real-time PCR for SARS-CoV-2 on samples from the three cases showed cycle threshold (Ct) values <20 and S-gene target failure (SGTF), which is considered a robust proxy for the SARS-CoV-2 B.1.1.7 lineage [ 19 ]. In all three cases, prolonged viral shedding was reported ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time PCR for SARS-CoV-2 on samples from the three cases showed cycle threshold (Ct) values <20 and S-gene target failure (SGTF), which is considered a robust proxy for the SARS-CoV-2 B.1.1.7 lineage [ 19 ]. In all three cases, prolonged viral shedding was reported ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that subjects infected by SARS-CoV-2 VOC 202012/01 are at a higher risk of severe COVID-19, hospitalization, and death [ 19 , 20 ]. Therefore, the severity of COVID-19 in the SOT recipients, as described here, could be related to infection with the B.1.1.7 variant.…”
Section: Discussionmentioning
confidence: 99%
“…Among the limits of our paper, we can report the following: a) only a late timepoint was analyzed for this patient in terms of virus sequencing: therefore, we it cannot formally be proven that variation originated in this specific individual, although it is likely. In this regard, we underline as methods of massive parallel sequencing have not been immediately implemented in laboratory tracing in our region as it happened either in other Italian areas or countries ( 26 , 27 ): b) the functional impact of our alteration has been extrapolated by data regarding other point alteration falling in the same domain. Further studies have been planned to better characterize this new variant, possibly in animal or cellular models: these experimental procedures take time and are also expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study using data from Southern Italy estimated an adjusted odds ratio of 3.44 (1.76, 6.75) for hospitalization for Alpha with respect to original wildtype (21), and did not directly report on the presence or absence of an age trend.…”
Section: 1 a L P H Amentioning
confidence: 99%
“…Of the included studies, four were conducted in England (15)(16)(17)(18), and will be numbered in the tables that follow. One study was conducted in Denmark (19), one in Ontario, Canada (20), one in Southern Italy (21), and one in Northwest Spain (22). One includes data from seven European national surveillance systems (23).…”
mentioning
confidence: 99%